Pengembangan model bimbingan belajar untuk meningkatkan motivasi berprestasi siswa SMPN 1 Enrekang - Sulaiman, Fitriyani (Program Studi bimbingan Konseling PPs UNM Makassar, 2016)
Development research was conducted at SMPN 1 Enrekang with 10 research subject. The problem of the study was students still have low achievement motivation. The study aimed at (1) examining student needs analysis, (2) producing acceptable tutoring model on the aspects of usefulness, feasibility, an accuracy, and (3) examining the effectiveness of tutoring model to enhance achievement motivation. The study employed research and development approach. The development procedure referred to Borg and Gall’s. Data were collected through interview, direct observation, and questionnaire. Data of the study were analyzed qualitatively. The tutoring guideline had been tested by three expert and confirmed as feasible, accepted, and could be tested to the students. Thus, the results of the study were (1) low achievement motivation of the student, (2) produce acceptable tutoring model on the aspects of usefulness, feasible, and accuracy, and (3) the learning guidance model was effective to enhance students’ achievement motivation in SMPN 1 Enrekang.